2012
DOI: 10.1039/c2cp42225e
|View full text |Cite
|
Sign up to set email alerts
|

How low can you go? Minimum energy pathways for O2 dissociation on Pt(111)

Abstract: Many DFT studies of O(2) dissociation on Pt(111) give conflicting information on preferred paths and final states. Here we report large p(4 × 4) unit cell minimum energy pathway evaluations and compare O(2) adsorption and dissociated states on Pt(111). Calculations reveal how the pathways for O(2) dissociation starting from top-fcc-bridge, top-hcp-bridge, and top-bridge-top sites are interconnected. They also provide a direct reaction pathway for the dissociation of an O(2) molecule from a top-fcc-bridge into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 44 publications
8
34
0
Order By: Relevance
“…We have found that O 2 dissociation activation energies, E a,i , for these dissociation events on Pt(111) can be correlated to the overall reaction energy ΔE i using a BEP relationship. 5,6,13…”
Section: Introductionmentioning
confidence: 99%
“…We have found that O 2 dissociation activation energies, E a,i , for these dissociation events on Pt(111) can be correlated to the overall reaction energy ΔE i using a BEP relationship. 5,6,13…”
Section: Introductionmentioning
confidence: 99%
“…At least at low O coverage, O 2 automatically dissociates on low-index Pt surfaces such as (111), (100), (321) [48][49][50]. Although O adsorption is much stronger than CO adsorption, their coadsorption has exemplified the change of favorable binding site of O.…”
mentioning
confidence: 98%
“…Computer simulation provides an alternative method to explore the ORR mechanism and a theoretical supplement for state-of-art experimental techniques. Extensive theoretical studies on the O 2 adsorption and ORR mechanism have been reported [16][17][18][19][20][21][22][23]. However, most of them employed the DFT method, which cannot explicitly consider the effect of bulk solvent and obtain the dynamic information of adsorption interface.…”
Section: Introductionmentioning
confidence: 98%